Development and Performance Evaluation of a Biomass Gasification System for Ceramic Firing Process - Punnarapong P. (2017)
© 2017 The Authors. Ceramic products are manufactured in many countries worldwide. Ceramic manufacturing industry is vital in terms of employment and economics. The industry is very energy intensive, consuming large amount of fuels. Liquefied petroleum gas (LPG) and natural gas are usually used, representing a significant portion of the total production cost. Switching to alternative gaseous fuel such as biomass derived producer gas may result in lower energy cost. Producer gas generated from biomass gasification process contains H 2 , CO and CH 4 which are combustible. Under carefully controlled conditions, burning of producer gas can provide suitable firing atmospheres for manufacture of ceramic products. In this work, attempt has been made to develop a 600 kW th biomass gasification system for ceramic firing. Woodchips were used as fuel. Product gas was generated and analyzed for its composition and energetic content. Firing of this fuel gas in place of LPG with modified gas burners in a firing chamber and preliminary testing at a local ceramic factory were carried out and demonstrated. It was found that required heat outputs and high temperature conditions were realized. Acceptable quality of the ceramic products was obtained. A simple economic analysis yielded an attractive return on investment. This proved to be a very promising energy option for substitution of fossil based gaseous fuels in ceramic industry.